2021
DOI: 10.1186/s12985-021-01656-3
|View full text |Cite
|
Sign up to set email alerts
|

Case report: hepatitis in a child infected with SARS-CoV-2 presenting toll-like receptor 7 Gln11Leu single nucleotide polymorphism

Abstract: Background Covid-19 has the respiratory tract as the main target of infection, and patients present mainly dyspnea, pneumonia, dry cough, and fever. Nevertheless, organs outside the respiratory tract had been reported in recent studies, including the gastrointestinal tract and liver. The host innate immune system recognizes pathogen-associated molecular patterns (PAMPs) through their pattern recognition receptor (PRRs). Toll-like receptor 7 (TLR-7) is a pattern recognition receptor recognizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
0
21
0
2
Order By: Relevance
“…When some polymorphisms (NSP1 K194R and NSP13 A335V) present in MHV-JHM.SD were introduced into an MHV-JHM.WU-like virus, the viral replication in the liver was diminished, but there is no data on the brain viral titers or overall lethality and weight loss that mice experienced [ 97 ]. Such results are difficult to extrapolate to SARS-CoV-2, which seems not to be as neurovirulent [ 148 ] and does not readily replicate in the liver in most individuals [ 149 ]. In fact, SARS-CoV-2, SARS-CoV MA15 and Urbani and MERS-CoV are primarily respiratory viruses, but MHV-A59 and MHV-JHM have a broader tropism and replicate effectively in the brain, spleen and liver [ 149 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When some polymorphisms (NSP1 K194R and NSP13 A335V) present in MHV-JHM.SD were introduced into an MHV-JHM.WU-like virus, the viral replication in the liver was diminished, but there is no data on the brain viral titers or overall lethality and weight loss that mice experienced [ 97 ]. Such results are difficult to extrapolate to SARS-CoV-2, which seems not to be as neurovirulent [ 148 ] and does not readily replicate in the liver in most individuals [ 149 ]. In fact, SARS-CoV-2, SARS-CoV MA15 and Urbani and MERS-CoV are primarily respiratory viruses, but MHV-A59 and MHV-JHM have a broader tropism and replicate effectively in the brain, spleen and liver [ 149 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such results are difficult to extrapolate to SARS-CoV-2, which seems not to be as neurovirulent [ 148 ] and does not readily replicate in the liver in most individuals [ 149 ]. In fact, SARS-CoV-2, SARS-CoV MA15 and Urbani and MERS-CoV are primarily respiratory viruses, but MHV-A59 and MHV-JHM have a broader tropism and replicate effectively in the brain, spleen and liver [ 149 ]. The scale of attenuation used in this work reflects this issues.…”
Section: Discussionmentioning
confidence: 99%
“…Infrared light therapy has been shown to decrease TLR4-dependent induction of IL-6, IL-8, TNF-α, INF-α, and INF-β in COVID-19 hyperinflammation [61]. It was observed that a child with hepatitis after SARS-CoV-2 infection had a polymorphism, Gln11Leu (rs179008), in TLR7 [62], which could impair an efficient initial immune response. Elevated cytokine levels have been linked to SARS-CoV-2 infection in adults (median age, 51 years) [63].…”
Section: Tlr Response To Sars-cov-2 Infectionmentioning
confidence: 99%
“…The patients (n = 8) with MIS having a high level of inflammatory markers which required admission to critical care, and three patients had an adverse outcome [ 13 ]. Pessoa and his coworkers have reported the first case of hepatitis in a male child infected with SARS-CoV-2 that has the Toll-like receptor 7 (TLR-7) Gln11Leu single nucleotide polymorphism, which could impair an efficient initial immune response [ 14 ]. Furthermore, Antala and coworkers have reported severe hepatitis in four previously healthy children as the primary manifestation of SARS-CoV-2 infection without respiratory symptoms, out of which two patients had acute liver failure [ 15 ].…”
mentioning
confidence: 99%